2020
DOI: 10.46341/pi2020006
|View full text |Cite
|
Sign up to set email alerts
|

Biometric characteristics of fruits and leaves of Cornus officinalis Siebold et Zucc. genotypes in the M.M. Gryshko National Botanical Garden of the NAS of Ukraine

Abstract: In the context of global climate change, the current strategy of agroeconomics focuses on the introduction of unique plant species and the selection of new commercially important cultivars adapted to the dramatic weather changes. Cornus officinalis (Cornaceae) has Chinese origin, its reintroduction at the M.M. Gryshko National Botanical Garden, National Academy of Sciences of Ukraine started in 1993. The objectives of this research were: to investigate the biometric parameters of fruits and leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Gryshko National Botanical Garden of NAS of Ukraine (NBG) were the objects of these investigations. Plants CmCo-01 and CmCo-02 are artificial hybrids from crossing C. officinalis × C. mas [ 58 ]. The raw material was collected in the period of full ripeness (September 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Gryshko National Botanical Garden of NAS of Ukraine (NBG) were the objects of these investigations. Plants CmCo-01 and CmCo-02 are artificial hybrids from crossing C. officinalis × C. mas [ 58 ]. The raw material was collected in the period of full ripeness (September 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Studies conducted in vitro and in vivo have shown a multi-faceted protective effect of fruit extract against diabetes and its complications, in particular a diabetic nephropathy. Decoctions of fruits and leaves are used in folk medicine as a tonic, stimulating and astringent (Klymenko, 2002;Klymenko and Ilyinska, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, we have researched cultivar Etude, which is an artificial hybrid from crossing C. officinalis × C. mas. Genotype obtained from grafting C. officinalis on C. mas (Klymenko and Ilyinska, 2020).…”
Section: Introductionmentioning
confidence: 99%